Effects of polyvalent immunoglobulins in patients with recurrent pregnancy loss and antibodies to the choriocarcinoma cell line JEG-3. (November 2015) - Rogenhofer, Nina; von Schönfeldt, Viktoria; Ochsenkühn, Robert; Sili, Felicia; Thaler, Christian J.
Abstract: Objective: The benefit of polyvalent immunoglobulins (IVIG) for patients with recurrent pregnancy loss (RPL) is controversially discussed. Anti-trophoblast antibodies as an expression of immune pathology have been associated with RPL. We investigated whether the antibody activity against the choriocarcinoma cell line JEG-3 in RPL patients is influenced in vitro by IVIG. Study design: Sera of 110 unexplained RPL patients with positive anti-JEG-3 antibodies were coincubated with IVIG in different concentrations (10 mg/ml, 20 mg/ml, 40 mg/ml). Coincubation with human albumin in identical concentrations served as control. Anti-JEG-3 reactivity was measured by using flow cytometry in comparisons with two in-house standards antibody probes of low and high reactivity as described before. Anti-JEG-3 reactivity above the 95% confidence interval of controls was defined as positive. Results: Incubating RPL sera with 10 mg/ml IVIG significantly decreased anti-JEG-3 activity ( p  < 0.001). Increasing IVIG concentration to 40 mg/ml resulted in a slightly additionally reduction ( p  = 0.42). In contrast, coincubation with albumin in identically concentrations did not affect anti-JEG-3 activity ( p  > 0.40). Conclusion: Coincubation with IVIG in vitro leads to a significant suppression of anti-JEG-3 activity in the sera of RPL patients.